State of the art in functionally graded materials. (15th April 2021) - Boggarapu, Vasavi; Gujjala, Raghavendra; Ojha, Shakuntla; Acharya, Sk; Venkateswara babu, P.; Chowdary, Somaiah; kumar Gara, Dheeraj
Highlights: Technological advancements in functionally graded materials. Comparison of various homogenization schemes. Review on analysis of functionally graded structures. Suggested future scope in the analysis of functionally graded structures. Review on various fabrication methods of functionally graded materials along their mechanical and tribological performance. Abstract: This paper discourses an overview of the recent advancements in functionally graded materials (FGMs) research. The paper also disseminates on the key researches that are carried out in the scientific community on the development of manufacturing and modelling of functionally graded materials. The rationale of the current work is to emphasize the selection of materials, processing techniques and analytical modelling and applications of FGMs. Alongside, challenges involved in developing these materials towards various aspects of scientific and technological fields will be addressed.